Variação e mudança linguística: panorama e perspectivas da sociolinguística variacionista no Brasil - Salomão, Ana Cristina Biondo [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2011)
Since the 1970s many research groups have emerged in Brazil in the area of Sociolinguistics, seeking to investigate language in relation to social factors that distinguish different speech communities to deconstruct the idea of linguistic homogeneity. Many of the works have been based on variationist sociolinguistics (LABOV, 2008 [1972]), for which variation and change are inherent to languages, i.e., heterogeneous structures are part of the speakers’ linguistic competence, as a cultural phenomenon motivated by linguistic and extralinguistic factors. Our aim, in this article, is to address the paths of Sociolinguistics since its beginning as a science, focusing mainly on the variationist strand, by recalling its key-concepts and methodology, and to present an overview of the research works conducted in Brazil in this field nowadays.

Desde a década de 1970 inúmeros grupos de pesquisa surgiram no Brasil na área da Sociolinguística, buscando investigar a linguagem relacionando-a a fatores sociais que distinguem diferentes comunidades de fala para a desconstrução da ideia de homogeneidade linguística. Muitos dos trabalhos desenvolvidos têm suas bases na sociolinguística variacionista (LABOV, 2008[1972]), para a qual a variação e a mudança são inerentes às línguas, como um fenômeno cultural motivado por fatores linguísticos e extralinguísticos. Pretendemos, aqui, retomar os caminhos percorridos pela Sociolinguística desde seu início como ciência, atendo-nos principalmente à corrente variacionista, revisitando seus conceitos-chave e sua metodologia, e apresentar um panorama dos trabalhos desenvolvidos nesta linha de pesquisa no Brasil na atualidade.
Language variation and change: overview and perspectives of variationist sociolinguistics in Brazil
Keywords: Variationist sociolinguistics; Language variation and change; Research groups; Sociolinguística variacionista; Variação e mudança linguística; Grupos de pesquisa